Investing in renewable energy : making money on green chip stocks - Siegel, Jeffrey, 1970-; Hodge, Nick, 1983-; Nelder, Chris, 1964- (Hoboken, N.J. : John Wiley & Sons, 2008)
Investment advisor Jeff Siegel maintains that in the next 10 to 15 years, the price of renewable energy will fall dramatically, allowing the industry not only to compete on a level playing field, but to offer energy at a price that will be cheaper than oil, natural gas, and coal. Investors who understand this market will be the first to uncover some very profitable opportunities. Filled with in-depth insights and practical advice, this book will show readers how to tap into this market early, and logically, in order to capture unparalleled profits.--From publisher description.
0
Includes bibliographical references (p. 221-243) and index.
Keywords: Energy industries; Renewable energy sources; Clean energy industries; Commodity futures; Investments